2014
DOI: 10.1017/s0016756813001003
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon geochronology of pre-Cretaceous strata: tectonic implications for the Jiangnan Orogen, South China

Abstract: Fifteen sandstone samples taken from pre-Cretaceous strata of the Yangtze Block are analysed to constrain the evolution of the South China Block, especially the assembly between the Yangtze and Cathaysia blocks. The results show that the maximum depositional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 134 publications
1
14
0
Order By: Relevance
“…The North and South China blocks have different age composition of their basement crusts (e.g. Lei & Shu, ; Li et al, ; Su et al, ; Zhao et al, ; Zhu, Zhu, Ge, & Wang, ), and the main difference between the two blocks is observed in the Neoproterozoic interval; i.e. abundant in South China, whereas absent in North China.…”
Section: Precambrian Zirconsmentioning
confidence: 99%
See 1 more Smart Citation
“…The North and South China blocks have different age composition of their basement crusts (e.g. Lei & Shu, ; Li et al, ; Su et al, ; Zhao et al, ; Zhu, Zhu, Ge, & Wang, ), and the main difference between the two blocks is observed in the Neoproterozoic interval; i.e. abundant in South China, whereas absent in North China.…”
Section: Precambrian Zirconsmentioning
confidence: 99%
“…The latest zircon data indicate that the North China craton potentially contains even a Hadean crust in its northeastern part (Z. Li, Chen, & Wei, ); however, no Neoproterozoic granitoids occur. In contrast, the South China block is characterized by dominantly Proterozoic crust, with minor components of Archean crust (Lei & Shu, ; H. L. Li et al, ; Su et al, ; Zhao et al, ). In particular, the northwestern half (Yangtze sub‐block) is occupied dominantly by Neoproterozoic crust that is younger than 1.0 Ga, in apparent coincidence with the so‐called Pan‐African orogenic episodes to have formed Gondwana (e.g.…”
Section: Precambrian Zirconsmentioning
confidence: 99%
“…The Jishou diabase is 134 ± 2.3 Ma old, which is consistent with the Yanshanian age reported by BGMRH (). Meanwhile, no Cretaceous detrital zircon ages are detected in its surrounding strata, and therefore it cannot be captured from country rocks (Su, Dong, Zhang, Li, Chen, & Cui, ). The Jishou diabase is located on an uplifted orogen of the XTZ.…”
Section: Discussionmentioning
confidence: 99%
“…The SCB comprises two major continental blocks: the Yangtze Block in the northwest and the Cathaysia Block in the southeast, separated by the Jiangnan Orogen, whose western part is also named the XTZ (Figure ; Dong et al, ; Su, Dong, Zhang, Li, Chen, & Cui, ; Su, Dong, Zhang, Li, Chen, Li, et al, ; Su, Dong, Zhang, Li, Chen, Ma, et al, ). The SCB experienced successive subduction/collision events during the Mesozoic.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation